Leveraging Smartphones for Distributed Global Navigation Satellite System Post-Processing - Zdraveski, Vladimir; Gushev, Marjan; Kostoska, Magdalena; Ivanovski, A (IEEE, 2021)
Smartphones play an important role in today’s society. Although their performance increases rapidly, we are witnesses of their small average daily usage. In this paper, we focus on executing post-processing tasks required for the growing amount of daily generated GNSS data. The research hypothesis is to check whether we can take an advantage to use smartphones while they are idle for such kind of post-processing. We have realized a prototype model and measured the performance as a proof of concept use-case to provide evidence if such an implementation is effective.
Keywords: smartphones, grid computing, GNSS postprocessing